Open Forum for CSO Development Effectiveness - From Latin America Civil Society Organizations (2010)
Since the very beginning of the Open Forum process, the Latin American and Caribbean (LA/C) region has been participating in the dynamics of this work, at the global as well as regional and national levels. This publication presents part of the results from this participation, and in this way the LA/C region presents its contribution to the Forum’s First General Assembly (Istanbul, Turkey, September 28-30, 2010).